Wpływ działalności bobra europejskiego Castor fiber L. na zmiany stosunków wodnych na Polesiu Zachodnim - Omelczuk, Łukasz; Kozieł, Marcin (Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2017)
Beavers are one of the few species that, due to their engineering capabilities, can make significant changes in the natural environment. These animals contribute to changes in water conditions in a catchment area by raising dams on watercourses. Beavers slow down the drainage of water to surface and underground retention. The main aim of the study was the inventory of changes in the water conditions caused by the activity of beavers in the area of the Polesie Zachodnie region. It presents the results of field observations carried out at six sites in Mosty and Żuków villages. The observations were conducted from October 2015 to June 2016. In these places numerous beaver ponds were found, which were then measured in QGIS 2.14 programme. Other changes in the hydrography of this area have also been identified – the formation of a new watercourse or the initiation of meander formation. In addition to the obvious changes in vegetation resulting from the feeding habits of animals, vegetation has been observed following changes in water conditions (e.g. the emergence of new wetland species).
Keywords: European beaver Castor fiber L.; Polesie Zachodnie; water conditions